Positive Story: Building Self-Confidence in Elementary School Children Through Reinforcement - Azzarah, Aulia; Wicaksono, Awang Setiawan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Schools ensure that students acquire knowledge and skills through various activities, both academic and non-academic, to help them achieve their full potential. However, in addition to intelligence, learning success also depends on a sense of responsibility and self-confidence, as well as self-confidence. Self-confidence plays an important role in children's daily lives, especially when they are in a new environment or facing a situation they have never experienced before. This study aims to identify changes in students' self-confidence levels, as well as evaluate the effect of positive reinforcement on their ability to tell stories with confidence. Using a Classroom Action Research (CAR) approach, this study observed students and applied a positive reinforcement storytelling method to improve their self-confidence. The results of this study indicate that the positive reinforcement storytelling method significantly improved students' self-confidence, as seen from higher scores and positive behaviors that emerged. This study presents an effective teaching method to improve students' self-confidence, providing important insights for educational practices that support students' social and emotional development in the classroom. The implications of this study are able to help the development of educational psychology by emphasizing the importance of an interactive and holistic approach to improving students' self-confidence, which can ultimately have an impact on academic performance.Sekolah memastikan bahwa siswa memperoleh pengetahuan dan keterampilan melalui berbagai kegiatan, baik akademik maupun non-akademik, untuk membantu mereka mencapai potensi terbaik mereka. Namun, selain kecerdasan, keberhasilan belajar juga bergantung pada rasa tanggung jawab dan keyakinan terhadap diri sendiri, serta rasa percaya diri. Kepercayaan diri memiliki peranan penting dalam kehidupan sehari-hari anak, terutama saat mereka berada di lingkungan baru atau menghadapi situasi yang belum pernah dialami. Penelitian ini bertujuan untuk mengidentifikasi perubahan dalam tingkat kepercayaan diri siswa, serta mengevaluasi pengaruh penguatan positif terhadap kemampuan mereka dalam bercerita dengan percaya diri. Menggunakan pendekatan Penelitian Tindakan Kelas (PTK), penelitian ini mengamati siswa dan menerapkan metode cerita dengan reinforcement positive untuk meningkatkan rasa percaya diri mereka. Hasil dari penlitian ini menunjukkan bahwa metode bercerita dengan reinforcement positive secara signifikan meningkatkan kepercayaan diri siswa, yang dapat dilihat dari skor yang lebih tinggi dan perilaku positif yang muncul. Penelitian ini menyajikan metode pengajaran yang efektif untuk meningkatkan rasa percaya diri siswa, memberikan wawasan penting bagi praktik pendidikan yang mendukung perkembangan sosial dan emosional siswa di dalam kelas. Implikasi penelitian ini mampu membantu perkembangan psikologi pendidikan dengan menekankan pentingnya pendekatan interaktif dan holistik untuk meningkatkan rasa percaya diri siswa, yang pada akhirnya dapat berdampak pada kinerja akademik.